Deep Thermohaline Circulation Across the Closure of the Central American Seaway. Issue 12 (23rd December 2020) - Öğretmen, N.; Schiebel, R.; Jochum, K. P.; Stoll, B.; Weis, U.; Repschläger, J.; Jentzen, A.; Galer, S.; Haug, G. H.
Abstract: The closure of the Central American Seaway (CAS) resulted in changes of ocean‐climate dynamics since the late Miocene following the uplift of northern Andes. Reconstructing the bottom‐water temperatures (BWTs) of the Caribbean Sea illustrates feedbacks of the closure on the ocean‐climate system including deep‐water dynamics of the Caribbean Sea. Here, Mg/Ca‐derived BWTs of the Plio‐Pleistocene Caribbean Sea from the benthic foraminifer Cibicidoides wuellerstorfi are presented for the first time and interpreted along with Na/Ca and Sr/Ca as proxies of salinity and continental input, respectively. Our results highlight several warm (93, Gi15‐19, and N1) and cool (92, M2, Gi20, and CN4) marine isotope stages (MISs). Accordingly, changes in the circulation of deep‐water masses during the CAS closure developed in four main time intervals: (I) between 5.2 and 4.1 Ma (million years ago) BWT was ~1.1°C, (II) 4.1–3.2 Ma ~2.1°C, (III) 3.2–2.7 Ma ~2.7°C, and (IV) 2.7–2.2 Ma ~2.1°C. Relatively higher, gradually increased temperatures between 3.2 and 2.7 Ma correspond to late Pliocene warmth and restricted inflow of Pacific waters into the Caribbean due to shoaling of the CAS. In addition, Sr/Ca values reveal gradually escalating terrigenous input until 2.7 Ma most likely related to the increased river discharge in response to the Andean uplift. The gradual decrease of the BWTs from 2.7 Ma may have resulted from the onset of Northern Hemisphere Glaciation. Overall, BWTs match with previous sea surface temperatures from the planktic foraminifer Neogloboquadrina dutertrei . The BWTs presented here confirm intensified thermohaline circulation during the overall Pliocene warmth with increased bottom‐water Na/Ca values indicating enhanced salinity. Key Points: Mg/Ca‐derived temperatures of the Caribbean bottom waters from C. wuellerstorfi across the Pliocene closure of the CAS are presented A novel salinity proxy from benthic foraminifers to reconstruct past changes of thermohaline circulation of the Caribbean Sea is applied fs‐LA‐ICP‐MS trace element analyses on single foraminifers yield significant and reproducible results on paleoceanography and paleoclimate